Hunter-gatherers of the Pleistocene/Early Holocene transition of Jaywamachay, Ayacucho - Yataco Capcha, Juan (2023)
Between 1966 and 1968, Richard MacNeish led the "Ayacucho Archaeological-Botanical Project" program in the Ayacucho basin, Huamanga province. There, they found more than 450 sites with human occupations. The Jaywamachay eaves stand out for their exhumed archaeological record. Excavations in 1969 and 1970 revealed the region's oldest human occupations. Detailed descriptions were published only for specimens corresponding to hunter-gatherers living during the last millennium of the Pleistocene and using Fell points. Due to the importance of these findings, the lithic remains (n = 4,388) contained in the twelve earliest strata of the site that present an age ranging between 11,603 and 9,556 calibrated years before the present were organized and studied. The analysis allowed us to identify two clear artifactual sets of different techno-morphological characteristics and chronologies. Due to the similarities of the instruments and their association with consistent calibration dating, archaeological remains from strata H to J were left between ~≥10.3 - 9 kya by Early Holocene hunter-gatherers.  From J1 to J3, human occupations lived during the Pleistocene/Holocene transition between 12.6 and 10.2 kya, and used Fell Points. These records make Jaywamachay one of the most significant sites to learn about the earliest human groups that inhabited the Ayacucho basin in the past.